Population Policy Implications of Housing and Household Dynamics: Evidence from Nepal’s 2021 Census - Khatiwada, Padma P.; Lamichhane, Kamala (Molung Educational Frontier, 2026)
Nepal’s National Population Policy 2025 represents a strategic response to declining fertility and slowing population growth, drawing heavily on evidence from the 2021 National Population and Housing Census (NPHC). This paper examines how housing and household dynamics, as revealed by the census, are reflected in the new population policy. Using a qualitative policy analysis supported by census data, the study assesses policy alignment, gaps, and implications for fertility, migration, ageing, and regional equity. The findings indicate that although the policy acknowledges demographic decline, internal migration, and population ageing, housing affordability, changing household structures, and regional housing disparities remain weakly integrated into population management strategies. The paper argues that population policy objectives, particularly pronatalist measures, cannot be effectively achieved without addressing household-level living conditions. The study concludes that integrating housing, settlement planning, and household diversity into population policy is essential for sustainable and inclusive demographic development in Nepal.